Environmental law and the ecosystem approach maintaining ecological integrity through consistency in law - Platjouw, Froukje Maria (Routledge research in international environmental law., 2016)
The ecosystem approach embodies a concept of the environment which emphasizes the integrated components of nature as complex adaptive systems. This book examines the relationship between the architecture and design of environmental law and the implementation of the ecosystem approach as a means to maintain ecological integrity.